ANALISIS RASIO SOLVABILITAS DAN PROFITABILITAS TERHADAP PERUBAHAN LABA PADA PT.LATINUSA, Tbk TAHUN 2014 – 2018 - Noviyanti Wulandari Sitepu (Universitas Gajayana Malang, 2018)
The formulation of the problem in this study are: 1) How does the influence of Debt To Asset Ratio on changes in earnings of PT. Latinusa, Tbk in 2014-2018? 2) How does the influence of Debt To Equity Ratio on changes in earnings of PT. Latinusa, Tbk in 2014-2018? 3) How does the influence of Net Profit Margin on changes in profits of PT. Latinusa, Tbk in 2014-2018? 4) What is the effect of Return On Equity (ROE) on changes in earnings of PT. Latinusa, Tbk in 2014-2018? 5) How does the effect of Return On Total Assets (ROA) on changes in earnings of PT. Latinusa, Tbk in 2014-2018? The method used in this research is descriptive analysis method. Data collection techniques used are documentation and literature study, while data analysis techniques used in this study to assess the effect of the solvency ratio on earnings changes are Debt To Asset Ratio, Debt To Equity Ratio. Assessing the effect of the solvency ratio on earnings changes namely Net Profit Margin, Return On Equity and Return On Total Assets. Based on the results of the study